“A Labour of Love”: Active Lifestyle Entrepreneurship (Occupational Devotion) During a Time of COVID-19 - Wright, Richard Keith; Wiersma, Cindy; Ajiee, Richard Opara (Frontiers in Sports and Active Living, 2021)
The Novel Coronavirus (COVID-19) crisis management strategies adopted by world leaders across the globe in 2020 impacted the work-life balance of billions of people. Entire populations were forced to stay at home and maintain a safe distance from family members, friends, colleagues, and customers. Occupational devotion is defined as a feeling of strong, positive attachment to a form of self-enhancing employment, where achievement and fulfillment are high, and the core activity has such intense appeal that the line between this work and leisure is virtually erased. Although it is not a new concept, this area of the serious leisure perspective has been largely overlooked by scholars observing the world of sport events and entrepreneurship. Using Creative Analytical Practice (CAP), a post-qualitative methodology, we present the personal narrative of a New Zealand-based active lifestyle entrepreneur who, as a result of a nationwide COVID19 lockdown, was forced to re-assess his long-established occupational devotion. Our co-constructed story offers an emotive insight into the personal cost and consequences of finding yourself living in a lockdown.